Artificial intelligence, media and journalism: Between a good servant and a bad master - Tomić Boban; Bajić Predrag Đ. (CM. Communication and Media)
The increasingly rapid development o f tools and capabilities provided by generative artificial intelligence is influencing media and journalistic practices, with tendencies towards a drastic transformation o f media structures, and even entire media ecosystems. The use o f generative artificial intelligence tools in media production, as well as in other related professions, can bring significant benefits to the process of data collection, processing, fact-checking, technical refinement o f text, creating headline blocks, and other segments. It can also assist in generating and promoting pre-created authentic journalistic content on social media. However, it is crucial to always keep in mind that behind everything is human input, meaning that artificial intelligence is not the creator o f something entirely new but a processor based on available data and information previously stored by humans in online systems, emphasizing the ongoing essential role o f humans in these processes. On the other hand, there are limitations and potential dangers concerning the infinite possibilities o f misuse o f artificial intelligence, necessitating a more thorough regulatory framework to govern this area. This is not only due to the potential danger o f artificial intelligence surpassing humans but generally to establish order in a new human practice that exceeds previous potentials and capacities. Therefore, it is necessary to address ethical, regulatory, and self-regulatory issues, as well as media literacy.